2017
DOI: 10.21037/jtd.2017.09.122
|View full text |Cite
|
Sign up to set email alerts
|

CT findings of pulmonary nocardiosis: a report of 9 cases

Abstract: Lung consolidation and nodules/masses are the most common findings, but CT findings of pulmonary nocardiosis are diverse and nonspecific. In some clinical background, such as immunocompromised patients or with some underlying lung diseases, consolidation or nodules/masses with cavitation may suggest the possibility of pulmonary nocardiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Common CT thorax ndings in Pulmonary Nocardiosis were parenchymal nodules, consolidation, mediastinal lymphadenopathy with or without cavitation present in around 70% of patients. Above CT abnormality in immunocompromised patients with high clinical suspicion may suggest the likelihood of Pulmonary Nocardiosis (11). Con rmation of diagnosis is requiring identi cation and isolation of Nocardia spp.…”
Section: Resultsmentioning
confidence: 99%
“…Common CT thorax ndings in Pulmonary Nocardiosis were parenchymal nodules, consolidation, mediastinal lymphadenopathy with or without cavitation present in around 70% of patients. Above CT abnormality in immunocompromised patients with high clinical suspicion may suggest the likelihood of Pulmonary Nocardiosis (11). Con rmation of diagnosis is requiring identi cation and isolation of Nocardia spp.…”
Section: Resultsmentioning
confidence: 99%
“…They found nodules ( n = 13, 32.5%), cavitation ( n = 12, 30.0%), consolidation ( n = 9, 22.5%), and masses ( n = 5, 12.5%) but no lymph node enlargement. Liu et al also reported nine cases of pulmonary nocardiosis, with consolidation ( n = 8, 88.9%) and mass or nodule ( n = 6, 66.7%) being the most common CT findings , but only two patients had lymph node enlargement. As both mediastinal lymph node enlargement and a mass were present on CT, it took time to determine an accurate diagnosis.…”
Section: Discussionmentioning
confidence: 97%
“…Our patient presented cough, purulent sputum, and occasional chest pain that did not improve despite the prophylactic use of oral voriconazole for 20 days. Radiological imaging of pulmonary Nocardia is non-specific as well and is generally focused under the pleura with occasional presence of pulmonary consolidation, pulmonary infiltration, solitary or multiple nodules, and other changes and with easy formation of voids [ 16 ]. These symptoms and radiological imaging provided poor clues to distinguish Nocardia infection from infection by other pathogens (e.g., pulmonary actinomycosis, tuberculosis, fungus), vasculitis or malignant tumors.…”
Section: Discussionmentioning
confidence: 99%